New distributional record of Mymar taprobanicum Ward, 1875 (Hymenoptera: Mymaridae) from Malaysian Borneo - Fatimah Abang; Ahmad Irfan Abdul Razak (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
Knowledge of the microhymenopteran fauna of the Chalcidoid family, Mymaridae of Malaysia is very limited. This report provides a new distributional record of Mymar taprobanicum Ward, 1875, from Sarawak, East Malaysian Borneo. Four male specimens were collected through yellow pan traps in a residential area in Kuching in December 2016. Although widely known as an important parasitoid of rice pests, this species has never been reported from East Malaysian Borneo prior to this report.